Control emocional, estilo represivo de afrontamiento y cáncer: ansiedad y cáncer - Cano, Antonio (Psicooncología, 2005)
Cancer diagnosis can be considered as a powerful stressor that could provoke emotional reactions (especially anxiety and depression) even emotional disorders (anxiety and mood disorders). Relationship between cancer and these psychological factors is reviewed. Cancer patients present lower levels of anxiety but similar or higher levels of depression, assessed by self-report questionnaires, than their corresponding controls. Anxiety disorders present similar twelve-month prevalence in cancer patients and in general population, meanwhile mood disorders are more prevalent in cancer patients.